Comparison of PM2.5 Chemical Compositions during Haze and Non-haze Days in a Heavy Industrial City in North China - Menghui Li; Liping Wu; Xiangyan Zhang; Xinwu Wang; Wenyu Bai; Jing Ming; Chunmei Geng; Wen Yang (Aerosol and Air Quality Research)
Abstract This study aimed to determine the chemical composition, sources and contributing factors of airborne PM2.5 (particulate matter with an aerodynamic diameter ≤ 2.5 µm) during a haze episode in Zibo, a heavy industrial city in China. Samples of PM2 5 were collected 8-27 January 2018 and analyzed for water-soluble inorganic ions (WSIs), trace elements (TEs), organic carbon (OC) and elemental carbon (EC). The PM2.5 concentration was 76.78% higher during the haze (mean ± standard deviation [SD] = 211 ± 39 µg m−3) than before it (49 ± 38 µg m−3), and the dominant ions were NO3-, SO42- and NH4+. Additionally, an elevated TE concentration was observed during the episode (exceeding the pre- and post-haze values by 54.70% and 31.98%, respectively), with crustal elements (K, Al, Ca, Si, Na, Fe and Mg), the most abundant elemental components, accounting for 88.64%. Carbonaceous species (OC and EC) contributed 15.45% of the PM2.5 on haze days and slightly more on non-haze days. The NO3/SO42- and OC/EC ratios indicated that coal combustion and motor vehicle emission were the primary sources of pollution, and back-trajectory analysis revealed that the air masses over Zibo on haze days mainly originated in adjacent areas in Shandong Province and the Beijing-Tianjin-Hebei region (BTH). The haze episode was caused by a combination of unfavorable meteorological conditions, secondary formation, the accumulation of local pollutants, and peripheral transmission.